Hygiene habits and the condition of oral mucosa in patients using acrylic removable dentures - Smolana, Aleksandra; Szypowska, Anna; Wieczorek, Aneta; Ryniewicz, Wojciech; E. Loster, Jolanta (Journal of Stomatology, 2017)
Introduction. Prosthetic rehabilitation can be considered a success when it leaves the patient with a sense of well-being and when the patient is aware of the need for effective oral hygiene behaviour. Aim of the study. To analyse the relationship between oral hygiene habits and the condition of oral mucosa in people using acrylic removable dentures. Material and methods. The research involved sixty patients using acrylic dentures (30 women and 30 men). The study was based on a questionnaire to evaluate patients’ hygiene habits, and a clinical examination of the mucous membrane using Newton classification was carried out. The data were statistically analysed using Pearson’s chi-square test (p < 0.05). Results. The patients were aged between 41 and 84 years (mean 66.3 years). Brushing with toothpaste was the most frequent cleaning method (82%). Twentyseven patients (45%) did not remove their dentures at night. Upon clinical examination, 40% of the patients had healthy mucous membrane on the palate. The quality of denture hygiene did not vary significantly with age, gender, or the duration of prosthesis use. There is a significant correlation between the way the prosthesis is handled at night and denture stomatitis (p=0.001). Conclusion. Failure to maintain hygienic practices with regard to removable dentures has an influence on the condition of the oral mucosa. Wearing dentures overnight is the most significant factor in the development of pathological changes of the mucous membrane.